HUBUNGAN KECEMASAN TERHADAP KETEPATAN SERVIS ATAS ATLET BOLA VOLI PUTRI - Fekie Adila; Agus Sulastio; Puspa Sari; Muhammad Imam Rahmatullah; Ittaqwa Ittaqwa (Jurnal Education and Development, 2023)
The problem in this study is the number of errors that PBV Kapila junior female volleyball athletes make when serving, because athletes find it difficult to properly manage their anxiety during competitions. The population in this study consisted of all junior female volleyball athletes PBV Kapila using a total sampling technique of 12 athletes. This type of research uses quantitative with correlational methods, using a questionnaire that is completed by the athletes. Based on the results and discussion with the analysis of the product moment correlation test, the researcher can generally conclude that there is a relationship between anxiety and women's volleyball serve accuracy at Kapila Tanjung Pinang with the proven value of r count 0.966 > r table 0.735. Thus, there is a significant relationship between anxiety and the accuracy of Kapila Tanjung Pinang's women's volleyball serve.